(3TQM cJGH GdKeQIs - (3CMeO Hf jhSa cGJH Bd Whdhfs; (3HWdjehS GdMcje GdbdhPjs
(3ChdgG (B:s
(3bGd CMeO Hf jhSa GdMGSH bO MUQJ CjOc Gddg HGdCeS ef GdNhV ai cJGH GdKeQI haJM GdJChjd deYGfjI eGRGOfi MQUkG Ydi ESYGac HJaSjQg bGd HWdjehS Yde GdfLhe s
(3BNQgG (B:s
(3hCbGe EMOi YTQg djdg jSjQ ai cd djdI SjQkG eMShSkG aONd CHh GdMdfL HYO eOg eUQ hJSdW Ydi eUQ hfhGMjgG hMOK HeUQ LejY eG PcQg HWdjehS hGddg SHMGfg hJYGdi CYde s
(3HgG fXGe GdJYbjHIs
(3bQf GdfSN (B:s
(3GdbQf GdMGOj YTQs
(3JHUQI GdYfhGf (B:s
(3TQMs
(3JHUQGJ GdCUd (B:s
Keywords: (3Gdadcs